Analisis Pengaruh Customer Experience dan Persepsi Harga Terhadap Kepuasan Konsumen (Studi Kasus Pada Workshop Handgarage) - Akbar, Majdi (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This research aims to find out the influence of Customer Experience and Price Perception on consumer satisfaction in the Handgarage Workshop. This type of research is a causal associative research that aims to find out the influence of customer experience and price perception on customer satisfaction in the Handgarage Workshop. The data collection method is carried out through the distribution of questionnaires to consumers who have used the Handgarege Workshop service. The sample in this study is 15 respondents with non-probability sampling technique where the sample is taken non-randomly with purposive sampling. Data using multiple linear regression analysis method with the help of IBM SPSS 22 software application.The results of this study show that customer experience variables and price perception partially have a positive and significant effect on consumer satisfaction in handgarage workshops.